(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione - 2. Lo status dei cattolici orientali in Germania - 2.1. I fedeli della Chiesa ucraina - 2.2. Gli altri cattolici orientali - 3. Facoltà dei parroci latini di sposare coppie orientali? - 4. Chiesa di appartenenza dei figli di matrimoni misti - 4.1. Efficacia anche nella sfera giuridica latina? - 4.2. La situazione prima del motu proprio De concordia inter Codices - 4.3. La situazione dopo il motu proprio De concordia inter Codices - 5. Conclusioni. The Status of Oriental Catholics in Germany. A current challenge for the coordination of the two Codes ABSTRACT: According to an estimate by the Secretariat of the German Bishops’ Conference, about 200,000 members of fourteen different Eastern Catholic Churches currently live in Germany. A first large migratory wave with a lasting impact up to today emerged with members of the Ukrainian Greek Catholic Church in the first decades of the 20th century. Lately, due to migration from Syria and Iraq starting in 2015, a larger number of Eastern Catholics - estimated by some in the five-digit range - have arrived in Germany. The change brought about by migration poses new challenges for pastoral care and canon law in Germany. The Ukrainians have their own jurisdiction in the form of an Apostolic Exarchy. All other Oriental Catholics have been entrusted to local Latin ordinaries by a decree of the Congregation for the Oriental Churches according to can. 916, § 5, CCEO. Therefore, the solution of many legal questions requires a synopsis of both codes. Do Latin parish priests have the authority to celebrate marriages for Oriental couples per se? To which church do children from a mixed marriage belong? The motu proprio De concordia inter Codices did not answer all questions and has also brought new ones.